Evaluation of Gelatin Concentration Variations on the Porosity ofGreen Mussel Shell Hydroxyapatite Scaffolds - Firda Aulia Rahman; Widi Widayat (Universitas Negeri Semarang, 2026)
The increasing demand for scaffolds in orthopedic applications has driven research into locally sourced biomaterials. Thisstudy evaluates the effect of varying gelatin concentrations (2%, 3%, and 4% w/w) on the porosity of hydroxyapatite (HA) scaffolds synthesized from green mussel shells (Perna viridis). HA was synthesized through a calcination process at a temperature of 900°C, followed by microwave-assisted ultrasonic precipitation, yielding a phase purity of 98.4% as confirmed by X-ray diffraction (XRD). The composite scaffolds were fabricated by mixing HA with type B gelatin at threeconcentrations, molded into cylindrical molds (6 mm diameter × 6 mm height), and dried at 40°C for 24 hours. Porositywas measured using the Archimedes liquid displacement method with 96% ethanol. The results indicated porosity valuesof 57.4% ± 1.68%, 60.2% ± 2.97%, and 58.1% ± 1.15% for gelatin concentrations of 2%, 3%, and 4%, respectively. All formulations exceeded the lower limit of commercial scaffold porosity standards (35–50%), with the 4% formulationapproaching the upper limit of that range. This study demonstrates that HA derived from green mussel shells combinedwith gelatin produces scaffolds with a porosity comparable to commercial products, thereby offering an economical andsustainable alternative for bone tissue engineering applications.